2018
DOI: 10.3386/w24384
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Countryside via E-Commerce: Evidence from China

Abstract: This paper estimates the impact of the first nationwide e-commerce expansion program on rural households. To do so, we combine a randomized control trial with new survey and administrative microdata. In contrast to existing case studies, we find little evidence for income gains to rural producers and workers. Instead, the gains are driven by a reduction in cost of living for a minority of rural households who tend to be younger, richer and in more remote markets. These effects are mainly due to overcoming logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…By combining a randomized control trial with a new survey and administrative microdata, Couture et al (2020) show how fintech influences consumer welfare, with a specific focus on rural households in China during 2014-2018. They find that overall, access to e-commerce appears to offer economic gains to certain groups of the rural population and in certain places.…”
Section: Economic Impacts Of Fintech Development A) Positive Impact Omentioning
confidence: 99%
“…By combining a randomized control trial with a new survey and administrative microdata, Couture et al (2020) show how fintech influences consumer welfare, with a specific focus on rural households in China during 2014-2018. They find that overall, access to e-commerce appears to offer economic gains to certain groups of the rural population and in certain places.…”
Section: Economic Impacts Of Fintech Development A) Positive Impact Omentioning
confidence: 99%
“…With the development of the e‐commerce industry after 2008 in the village, young men and women alike have increased their income by running online shops on the Taobao platform, compared to working in the urban areas. In comparison to the older villagers, the youngsters are better educated and tech‐savvy, thereby being able to establish online shops and recruit their parents to work for their businesses (Couture et al ., 2018). It is in this context wherein young women have gained more economic resources to provide for their families, as managers of family online shops, than the women of their mother's generation.…”
Section: Methods and Datamentioning
confidence: 99%
“…In particular, since 2013 China has overtaken the United States becoming the global largest e‐commerce market (Ma et al ., 2016:6). Although there are ample studies centred on accounting for the rapid growth of e‐commerce in China (Lu et al ., 2015; Ma et al ., 2016; Li, 2017; Couture et al ., 2018), there has not been adequate scholarly attention given to whether and how the boom of e‐commerce has reshaped gender norms and gender relations (Yu and Cui, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, formal studies based on reliable microlevel data are rare, with a small number of exceptions, including, notably, Couture et al (2018) and Fan et al (2018). This probably has much to do with the fact that online sales data are too often available only from the platform on which the transactions take place.…”
Section: E-commerce Development In Rural China and Related Researchmentioning
confidence: 99%
“…Moreover, when assessing the actual impact of rural e-commerce development, the findings are revealing. As one of the only few academic studies that investigates this topic, Couture et al (2018) found that rural e-commerce resulted in stronger consumption-side effects as e-commerce terminals offered lower prices, greater convenience and increased product variety. For households, gains in household purchasing power were strongest for durable products.…”
Section: E-commerce Development In Rural China and Related Researchmentioning
confidence: 99%